Financing the extension of social insurance to informal economy workers The role of remittances - Kolev, Alexandre (OECD Development Centre Working Papers, 2021)
Informal employment, defined through the lack of employment-based social protection, constitutes the bulk of employment in developing countries, and entails a level of vulnerability to poverty and other risks that are borne by all who are dependent on informal work income. Results from the Key Indicators of Informality based on Individuals and their Households database (KIIbIH) show that a disproportionately large number of middle‑class informal economy workers receive remittances. Such results confirm that risk management strategies, such as migration, play a part in minimising the potential risks of informal work for middle‑class informal households who may not be eligible to social assistance. They further suggest that middle‑class informal workers may have a solvent demand for social insurance so that, if informality-robust social insurance schemes were made available to them, remittances could potentially be channelled to finance the extension of social insurance to the informal economy